Analisa Kualitas Aplikasi Computer Based Test Menggunakan Webqual 4.0 - Fitri Rachmita Utami; Besus Maula Sulthon (STMIK Budi Darma, 2024)
There are many information technology applications that are widely used, so the analysis process that we are currently using is one of them at the South Tangerang 1 State Vocational High School (SMK), which is one of the educational institutions in Indonesia which is committed to providing quality and relevant education with technological developments. In the midst of the rapid development of information and communication technology (ICT), the approach to educational evaluation must also change. This shift is reflected in the use of computer-based exams. Computer Based Test is an evaluation tool that utilizes computer technology to measure student knowledge and skills. At SMK Negeri 1 South Tangerang, computer-based exams have an important role in the context of modern education. The problem behind this research is that the Computer Based Test application service that has been implemented does not yet have sufficient evidence to state that the application is acceptable and considered by vocational school teachers and students. Users (class 10 students) don't understand much about the application, because they are not used to using it. For the application to be used only per year, it has not/does not automatically move to the following years, the admin/programmer must change the settings to move the settings by coding. The current problem is that the Telkomsel provider is blocking the application. If the test on CBT will be safe and run smoothly, you won't be able to screenshot or record layers and the complaint is that if you use the link/barcode you will be able to find out the answers and be able to screenshot and record layers. There are many possible errors in class and subject selection. This research measures the quality of the Computer Based Test application through the Webqual 4.0 dimensions (usability, information quality, interaction quality) and user satisfaction variables, namely teachers and students of SMK Negeri 1 South Tangerang. The data collection method uses primary data in the form of a questionnaire distributed to 305 respondents. Data processing was carried out by comparing manual calculations with calculations using SPSS. Based on data processing, it can be seen that user perceptions regarding ease of use, quality of information, quality of interaction are included in the unsatisfactory category. Based on the research results, it was found that these three variables had a positive and significant effect on user satisfaction. From the research results, it can be seen that the interaction quality variable provides the largest contribution, namely 67.28% of the other variables.